(untitled) - Jean Paul Tremblay (New York, 1989)
Chapter 1 presents a number of basic computing notion. Chapter 2 introduces the notion of algorithm and the first contructs of the algorithmic language. The notion of "flow of control" is introduced in chapter 3. Functions, procedures, the concept of array, string processing, structured design and programming style are the topics of chapter 4,5,6 and 7. Chapter 8 and 9 deal with the linear and nonlinear data structures.
Keywords: algorithms,data structures ( computer science )